Smoothness Metrics in Complex Movement Tasks - Gulde, Philipp; Hermsdörfer, Joachim (Frontiers in Neurology, 2018)
Smoothness is a main characteristic of goal-directed human movements. The suitability of ap-proaches quantifying movement smoothness is dependent on the analyzed signal’s structure. Recently, activities of daily living (ADL) received strong interest in research on aging and neu-rorehabilitation. Such tasks have complex signal structures and kinematic parameters need to be adapted. In the present study we examined four different approaches to quantify movement smoothness in ADL. We tested the appropriateness of these approaches, namely the number of velocity peaks per meter (NoP), the spectral arc length (SAL), the speed metric (SM) and the log dimensionless jerk (LDJ), by comparing movement signals from eight healthy elderly (67.1a±7.1a) with eight healthy young (26.9a±2.1a) participants performing an activity of daily living (making a cup of tea). All approaches were able to identify group differences in smoothness (Cohen’s d NoP=2.53, SAL=1.95, SM=1.69, LDJ=4.19), three revealed high to very high sensitivity (z-scores: NoP=1.96±0.55, SAL=1.60±0.64, SM=3.41±3.03, LDJ=5.28±1.52), three showed low within-group variance (NoP=0.72, SAL=0.60, SM=0.11, LDJ=0.71), two showed strong correlations between the first and the second half of the task execution (intra-trial R²s: NoP=0.22 n.s., SAL=0.33, SM=0.36, LDJ=0.91), and one was independent of other kinematic parameters (SM), while three showed strong models of multiple linear regression (R²s: NoP=0.61, SAL=0.48, LDJ=0.70). Based on our results we make suggestion towards use and limitations of the examined smoothness measures. In total the log dimensionless jerk proved to be the most appropriate in ADL, as long as trial durations are controlled.